Bempegaldesleukin plus nivolumab in first-line renal cell carcinoma: results from the PIVOT-02 study. Issue 4 (20th April 2022) - Tannir, Nizar M; Cho, Daniel C; Diab, Adi; Sznol, Mario; Bilen, Mehmet A; Balar, Arjun V; Grignani, Giovanni; Puente, Erika; Tang, Lily; Chien, David; Hoch, Ute; Choudhury, Arkopal; et al.
Abstract : Background: Immune checkpoint inhibitor-based combinations have expanded the treatment options for patients with renal cell carcinoma (RCC); however, tolerability remains challenging. The aim of this study was to evaluate the safety and efficacy of the immunostimulatory interleukin-2 cytokine prodrug bempegaldesleukin (BEMPEG) plus nivolumab (NIVO) as first-line therapy in patients with advanced clear-cell RCC. Methods: This was an open-label multicohort, multicenter, single-arm phase 1/2 study; here, we report results from the phase 1/2 first-line RCC cohort (N=49). Patients received BEMPEG 0.006 mg/kg plus NIVO 360 mg intravenously every 3 weeks. The primary objectives were safety and objective response rate (ORR; patients with measurable disease at baseline and at least one postbaseline tumor response assessment). Secondary objectives included overall survival (OS) and progression-free survival (PFS). Exploratory biomarker analyses: association between baseline biomarkers and ORR. Results: At a median follow-up of 32.7 months, the ORR was 34.7% (17/49 patients); 3/49 patients (6.1%) had a complete response. Of the 17 patients with response, 14 remained in response for >6 months, and 6 remained in response for >24 months. Median PFS was 7.7 months (95% CI 3.8 to 13.9), and median OS was not reached (95% CI 37.3 to not reached). Ninety-eight per cent (48/49) of patients experienced ≥1 treatment-related adverse event (TRAE) and 38.8% (19/49) had grade 3/4 TRAEs, most commonly syncope (8.2%; 4/49) and increased lipase (6.1%; 3/49). No association between exploratory biomarkers and ORR was observed. Limitations include the small sample size and single-arm design. Conclusions: BEMPEG plus NIVO showed preliminary antitumor activity as first-line therapy in patients with advanced clear-cell RCC and was well tolerated. These findings warrant further investigation.